Effect of Personality on Speaking Skills of Language Departement in SMA Negeri 1 Sawan - Cahyani, Kadek Dwi; Sutama, I Made; Rasna, I Wayan (Journal of Education Reseach and Evaluation, 2020)
This study aimed to know the effect of personality on speaking skills of Language Departement in SMA Negeri 1 Sawan. The population in this study were 106 students from 3 classes. Purposive Sampling was used as the sampling technique in this study. The number of samples in this study were 70 students, consisting of 30 introvert students and 40 students with extrovert personalities. The research method was Ex Post Facto research design. The data were analyzed by using T-test and the significance level was α = 0.005. The data were collected by using questionnaire and test. The results showed that there was an effect of personality on students’ speaking skills, with the significance value 0,000 less than 0.005 and it was seen from the average score of extrovert students’ speaking skills was 83.47 meanwhile the average score of introvert students’ speaking skills was 79.60. So, H0 is rejected and H1 is accepted.